Analisis Seismisitas Wilayah Turki sebagai akibat Aktivitas Seismo-Tektonik Patahan Anatolia - Dewi, Karlita; Fahmi, Muhammad Nurul; Realita, Arie (Prodi Fisika FMIPA Universitas Negeri Surabaya, 2025)
This study aims to analyze the seismicity and tectonic stress in Turkey based on earthquake data from the period 1924–2024 using the Frequency-Magnitude Distribution (FMD) approach with the ZMAP7.0 software. The study area is divided into four zones: Zone 1 (northwestern Turkey), Zone 2 (northeastern Turkey), Zone 3 (southwestern Turkey), and Zone 4 (southeastern Turkey). The parameters analyzed include the a-value for seismicity levels and the b-value for estimating subsurface tectonic stress. The results show that a-values ranging from approximately 5.80 to 6.03 are higher in Zones 3 and 4, indicating more frequent seismic activity in the southern regions. Conversely, Zones 1 and 2 have lower a -value, indicating less frequent earthquake occurrences. Lower b-value were found in the northern regions 0.58–0.66, suggesting higher tectonic stress and a greater potential for large earthquakes, particularly along the North Anatolian Fault. The southern regions exhibit higher b-values, reflecting lower stress levels and predominantly smaller earthquakes. For intermediate-depth sources, analysis was conducted only in Zone 3, where a low b-value indicates the potential for large earthquakes at these depths. This study contributes to a better understanding of Turkey's seismic characteristics and is essential for earthquake disaster mitigation planning.